Accuracy of Robotic and Frame-Based Stereotactic Neurosurgery in a Phantom Model - Spyrantis, Andrea; Woebbecke, Tirza; Rueß, Daniel; Constantinescu, Anne; Gierich, Andreas; Luyken, Klaus; Visser-Vandewalle, Veerle; Herrmann, Eva; Gessler, Florian; Czabanka, Marcus; Treuer, Harald; Ruge, Maximilian; et al. (Frontiers in Neurorobotics, 2022)
Background The development of robotic systems has provided an alternative to frame-based stereotactic procedures. The aim of this experimental phantom study was to compare the mechanical accuracy of the Robotic Surgery Assistant (ROSA) and the Leksell stereotactic frame by reducing clinical and procedural factors to a minimum. Methods To precisely compare mechanical accuracy, a stereotactic system was chosen as reference for both methods. A thin layer CT scan with an acrylic phantom fixed to the frame and a localizer enabling the software to recognize the coordinate system was performed. For each of the five phantom targets, two different trajectories were planned, resulting in 10 trajectories. A series of five repetitions was performed, each time based on a new CT scan. Hence, 50 trajectories were analysed for each method. X-rays of the final cannula position were fused with the planning data. The coordinates of the target point and the endpoint of the robot- or frame-guided probe were visually determined using the robotic software. The target point error (TPE) was calculated applying the Euclidian distance. The depth deviation along the trajectory and the lateral deviation were separately calculated. Results Robotics was significantly more accurate, with an arithmetic TPE mean of 0.53 mm (95% CI 0.41 – 0.55 mm) compared to 0.72 mm (95% CI 0.63 – 0.8 mm) in stereotaxy (p < 0.05). In robotics, the mean depth deviation along the trajectory was -0.22 mm (95% CI -0.25 – -0.14 mm). The mean lateral deviation was 0.43 mm (95% CI 0.32 – 0.49 mm). In frame-based stereotaxy, the mean depth deviation amounted to -0.20 mm (95% CI -0.26 – -0.14 mm), the mean lateral deviation to 0.65 mm (95% CI 0.55 – 0.74 mm). Conclusion Both the robotic and frame-based approach proved accurate. The robotic procedure showed significantly higher accuracy. For both methods, procedural factors occurring during surgery might have a more relevant impact on overall accuracy.